2-deoxy-glucose ameliorates the peritoneal mesothelial and endothelial barrier function perturbation occurring due to peritoneal dialysis fluids exposure - Pitaraki, Eleanna; Jagirdar, Rajesh M.; Rouka, Erasmia; Bartosova, Maria; Sinis, Sotirios I.; Gourgoulianis, Konstantinos I.; Eleftheriadis, Theodoros; Stefanidis, Ioannis; Liakopoulos, Vassilios; Hatzoglou, Chrissi; Schmitt, Claus P.; Zarogiannis, Sotirios G. (Biochemical and biophysical research communications, 2024)
Peritoneal dialysis (PD) and prolonged exposure to PD fluids (PDF) induce peritoneal membrane (PM) fibrosis and hypervascularity, leading to functional PM degeneration. 2-deoxy-glucose (2-DG) has shown potential as PM antifibrotic by inhibiting hyper-glycolysis induced mesothelial-to-mesenchymal transition (MMT). We investigated whether administration of 2-DG with several PDF affects the permeability of mesothelial and endothelial barrier of the PM. The antifibrotic effect of 2-DG was confirmed by the gel contraction assay with embedded mesothelial (MeT-5A) or endothelial (EA.hy926) cells cultured in Dianeal® 2.5 % (CPDF), BicaVera® 2.3 % (BPDF), Balance® 2.3 % (LPDF) with/without 2-DG addition (0.2 mM), and qPCR for αSMA, CDH2 genes. Moreover, 2-DG effect was tested on the permeability of monolayers of mesothelial and endothelial cells by monitoring the transmembrane resistance (RTM), FITC-dextran (10, 70 kDa) diffusion and mRNA expression levels of CLDN-1 to -5, ZO1, SGLT1, and SGLT2 genes. Contractility of MeT-5A cells in CPDF/2-DG was decreased, accompanied by αSMA (0.17 ± 0.03) and CDH2 (2.92 ± 0.29) gene expression fold changes. Changes in αSMA, CDH2 were found in EA.hy926 cells, though αSMA also decreased under LPDF/2-DG incubation (0.42 ± 0.02). Overall, 2-DG mitigated the PDF-induced alterations in mesothelial and endothelial barrier function as shown by RTM, dextran transport and expression levels of the CLDN-1 to -5, ZO1, and SGLT2. Thus, supplementation of PDF with 2-DG not only reduces MMT but also improves functional permeability characteristics of the PM mesothelial and endothelial barrier.
Online veröffentlicht 13 December 2023
Gesehen am 10.06.2024